Russia and sanctions evasion. Issue 4 (21st April 2022) - Unknown
Abstract : Russia is coordinating with other countries that have been targeted by international sanctions – Cuba, Iran, North Korea, Syria and Venezuela – and emulating their techniques to avoid some of the restrictions on international shipping and banking that have been imposed on Moscow since its decision to invade Ukraine in February 2022.